Rational design of improved dienophiles for in vivo tetrazine-trans-cyclooctene ligation - Neudecker, Tim; Scholtes, Jan Felix; Dreuw, Andreas (Chemical physics letters, 2016)
The inverse electron-demand Diels-Alder reaction of trans-cyclooctene and sym-tetrazine is a bioorthogonal reaction which has found widespread applications during the last decade, e.g. for fluorescent labeling of living cells. However, the use of this reaction is still limited due to the rapid isomerization of trans-cyclooctene to its unreactive cis-conformer. Using computational methods, we have derived two optimized derivatives of trans-cyclooctene, which pave the road to more efficient in vivo labeling of arbitrary proteins.
Gesehen am 05.12.2017